AB0761 DEMOGRAPHIC AND CLINICAL FEATURES OF JUVENILE-ONSET PSORIATIC ARTHRITIS: RESULTS FROM PsART-ID REGISTRY. (2nd June 2020) - Ergulu Eşmen, S.; Bayindir, O.; Kasapoğlu, E.; Bakirci, S.; Solmaz, D.; Kimyon, G.; Doğru, A.; Dalkiliç, E.; Özişler, C.; Can, M.; Akar, S.; Tarhan, E. F.; et al.
Abstract : Background: Although psoriatic arthritis (PsA) may be seen at any decades, juvenil onset PsA is relatively rare. Moreover, there were no more data about clinical features, treatments, and course in juvenile PsA when they reached to adult age. Objectives: The objective of this study was to assess and compare demographic and clinical features for juvenile onset PsA and adult onset PsA. Methods: PsART-ID is a multicenter, international database, investigating the disease characteristic in real life (1). Briefly, demographic data, PsA subtypes, uveitis, enthesitis, dactylitis, Co-morbidities, disease activity scores (TJC, SJC, VAS-pain, VAS patients and physician global assessments, VAS-fatigue, BASDAI), and functional status (HAQ-DI, BASFI) were recorded. Psoriasis and PsA starting age were noted, as well. Patients were classified as juvenile PsA or juvenile PsO (under 18 years old). Results were compared regarding to juvenile versus adult onset age. Results: Overall, 1644 PsA patients were included to study, 301/1644 (18.3%) patients had juvenile onset psoriasis. Of 39/1644 (2.4%) patients had juvenile onset PsA, as well. As expected, juvenile onset PsA patients were younger, however PsA disease duration were longer than adult onset PsA patients. There were no any difference between demographic and clinical data, except BMI and enthesitis were less frequently at the juvenile onset PsA groups. Although, ever csDMARD using were similar between two groups, however, juvenile onset PsA patients were used more frequently bDMARDs. Conclusion: Although psoriasis may be seen frequently in the juvenile age, juvenile onset PsA was not so frequent in our PsA cohort. Although, ever csDMARD using were similar between two groups, however, juvenile onset PsA patients were used bDMARDs more frequently. References: [1]Kalyoncu U et al. The Psoriatic Arthritis Registry of Turkey: results of a multicenter registry on 1081 patients. Rheumatology. 2017;56:279-286. Disclosure of Interests: Serpil ERGULU EŞMEN: None declared, Ozun Bayindir: None declared, esen kasapoğlu: None declared, Sibel Bakirci: None declared, Dilek Solmaz: None declared, Gezmiş Kimyon: None declared, Atalay Doğru: None declared, Ediz Dalkiliç: None declared, Cem Özişler: None declared, Meryem Can: None declared, Servet Akar: None declared, Emine Figen Tarhan: None declared, Sule Yavuz: None declared, Levent Kiliç: None declared, Orhan Küçükşahin: None declared, Ahmet Omma: None declared, Emel Gönüllü: None declared, Fatih Yildiz: None declared, Duygu Ersözlü: None declared, abdurrahman tufan: None declared, Muhammet Çinar: None declared, Abdulsamet Erden: None declared, Sema Yilmaz: None declared, Seval Pehlevan: None declared, Mehmet Tuncay Duruöz: None declared, Sibel Aydin: None declared, Umut Kalyoncu Consultant of: Abbvie, Amgen, Janssen, Lilly, Novartis, UCB